2011
DOI: 10.1097/bcr.0b013e318204b346
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin and Antifactor Xa Levels in Acute Burn Patients

Abstract: Altered pharmacokinetics in critically ill patients have been shown to result in inadequate enoxaparin dosing for venous thromboembolism (VTE) prophylaxis. In the burn unit, routine monitoring of antifactor Xa levels was implemented to ensure adequate VTE prophylaxis. The purpose of this study was to examine the appropriateness of enoxaparin dosing for VTE prophylaxis in this specialized patient population. The authors reviewed patients with acute burn injury from June 1, 2009, to October 20, 2009, who had eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 18 publications
1
44
0
1
Order By: Relevance
“…The presence of hypercoagulability after burn is well established, and both the rate of VTE (11) and the need for increased chemo-prophylactic dosing (33, 34) are correlated with increased burn size. Further, post-mortem human studies show microvascular thrombosis in multiple organs, specifically lung and renal tissues, leading to multiple organ dysfunction syndrome (MODS) and death (35, 36).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypercoagulability after burn is well established, and both the rate of VTE (11) and the need for increased chemo-prophylactic dosing (33, 34) are correlated with increased burn size. Further, post-mortem human studies show microvascular thrombosis in multiple organs, specifically lung and renal tissues, leading to multiple organ dysfunction syndrome (MODS) and death (35, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, standard prophylactic dosing of enoxaparin, a low-molecular weight heparin, has been shown to be inadequate in patients with large TBSA. Appropriate enoxaparin prophylaxis dose has been shown to correlate linearly with TBSA 31 . Thus, a proposed RCT should consider using antifactor Xa levels to guide prophylactic enoxaparin dosing.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, a recent study by Lin et al has shown that 79% of burn patients treated with standard doses of LMWH did not achieve the goal antifactor Xa levels, requiring higher LMWH doses that were correlated with the TBSA. 35 These data indicate that standard dosing of LMWH for VTE prophylaxis is inadequate for patients with acute burns. Furthermore, these patients may require a higher initial dose of LMWH in combination with routine monitoring of antifactor Xa levels.…”
Section: Discussionmentioning
confidence: 97%